Attentional bias towards threat in contamination fear: Overt components and behavioral correlates - Armstrong, Thomas (2011)
Recent research suggests that an attentional bias towards threat may play a causal role in obsessive-compulsive disorder (OCD) with contamination concerns. However, the attentional components involved in this bias, as well as its behavioral correlates, remain unclear. In the present study, eye movements were recorded in individuals high and low in contamination fear (HCF, LCF) during 30 s exposures to stimulus arrays containing contamination threat, general threat, pleasant, and neutral images. HCF individuals oriented gaze towards contamination threat more often than LCF individuals in initial fixations, and this bias mediated group differences in responding to a behavioral challenge in a public restroom. No group differences were found in the maintenance of gaze on contamination threat, both in terms of initial gaze encounters as well as gaze duration over time. However, the HCF group made shorter fixations on contamination threat relative to other image types. The implications of these findings for further delineating the nature and function of attentional biases in contamination-based OCD are discussed.